Six genetically distinct clades of Palola (Eunicidae, Annelida) from Lizard Island, Great Barrier Reef, Australia - Schulze, Anja (Zootaxa, 2015)
A total of 36 lots of Palola spp. (Eunicidae, Annelida) were collected during the Lizard Island Polychaete Workshop on Lizard Island, Great Barrier Reef, Queensland, Australia. Of these, 21 specimens were sequenced for a portion of the mitochondrial cytochrome c oxidase I gene. These sequences were analysed in conjunction with existing sequences of Palola spp. from other geographic regions. The samples from Lizard Island form six distinct clades, although none of them can clearly be assigned to any of the nominal species. Four of the six Lizard Island clades fall into species group A and the remaining two into species group B (which also includes the type species, Palola viridis). All sequenced specimens were characterized morphologically as far as possible and a dichotomous key was assembled. Based on this key, the remaining samples were identified as belonging to one of the clades.